2022
DOI: 10.3390/land11101714
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Mangrove Cover and Exposure to Coastal Hazards in Kenya

Abstract: Mangroves are effective carbon sinks, support coastal fisheries and provide wood and non-wood resources to coastal communities. They are threatened by natural and human-induced stresses including over-exploitation, conversion pressures, pollution and climate change. Understanding changes in this important ecosystem is essential to inform the sustainable management of mangroves and assess the implications related to the loss of ecosystem services. This study used global remote sensing mangrove forest data to qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…However, Kirui et al (2013) reported an annual net mangrove cover loss of 0.7% between 1985 and 2000 with the loss rate dropping to 0.28% between 2000 and 2010. Hamza et al (2022) estimated a mangrove cover loss of 0.15% per year between 2010 and 2016 indicating a trend of gradual reduction in loss of forest cover (Gitau et al, 2023).…”
Section: Projects In the Kenya Mangrove Ecosystemmentioning
confidence: 99%
“…However, Kirui et al (2013) reported an annual net mangrove cover loss of 0.7% between 1985 and 2000 with the loss rate dropping to 0.28% between 2000 and 2010. Hamza et al (2022) estimated a mangrove cover loss of 0.15% per year between 2010 and 2016 indicating a trend of gradual reduction in loss of forest cover (Gitau et al, 2023).…”
Section: Projects In the Kenya Mangrove Ecosystemmentioning
confidence: 99%
“…After six months, seedlings attained a shoot length of 8-24.5 cm (18.76 ± 0.46), with 4-12 (9.86 ± 0.21) leaves and 1-5 (3.93 ± 0.1) internodes. By the eighth month, the shoot length reached 24.73 ± 0.48 cm (range: 12.3-35.3 cm) with 11.45 ± 0.22 (8-14) leaves and 4.73 ± 0.11 (3)(4)(5)(6) internodes. Seedlings grown in the 3ʹʹ PVC recorded an average shoot length of 21.09 ± 1.17 cm (range: 12.6 -31.5 cm), with 11.44 ± 0.27 leaves (range: 10 to 14) and 4.72 ± 0.14 internodes (range: 4 to 6).…”
Section: Growth Performance Of the Replanted Mangrovesmentioning
confidence: 99%
“…Such changes are often amplified by loss and degradation of natural capital, including mangroves [4]. A study by [5] estimated 16% of Kenya coastline as highly exposed to natural hazards; and projecting a 41% escalation if marine ecosystems continue to be degraded . Global Projections indicate that the intensity of coastal hazards including storms and cyclones is likely to increase by 1-10% by 2030 -2080 [1,6].…”
Section: Introductionmentioning
confidence: 99%